The university effect in Valle del Cauca 2009: a multilevel analysis - Castillo Caicedo, Maribel; Monroy del Castillo, Ricardo David; Cardona Ceballos, Viviana (Universidad Pedagógica y Tecnológica de Colombia, 2015)
This article examines the university effect on wages of college graduates, i.e., if the university determines the level of income that the professional will receive in the labor market. Data for this research comes from “Survey of the labor market of professionals in the metropolitan area of Cali”, with a sample of 606 students from four universities of the city. Using a multilevel model with three levels (student, program and university) in order to capture effects of common factors groups, this study suggests the existence of a significant and high university effect. These results are consistent with the presence of signals in thelabor markets as proposed by theoryof signaling.